2020
DOI: 10.1007/s00345-020-03198-9
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous genitourinary lichen sclerosus signals a distinct urinary microbiome profile in men with urethral stricture disease

Abstract: Purpose Alterations in the urinary microbiome have been associated with urological diseases. The microbiome of patients with urethral stricture disease (USD) remains unknown. Our objective is to examine the microbiome of USD with a focus on inflammatory USD caused by lichen sclerosus (LS). Methods We collected mid-stream urine samples from men with LS-USD (cases; n = 22) and non-LS USD (controls; n = 76). DNA extraction, PCR amplification of the V4 hypervariable region of the 16S rRNA gene, and sequencing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…12 Differences in urinary microbiota composition between MGLSc patients and healthy controls have also in a separate study. 13 While our case demonstrates similarities with that reported by De Giorgi et al, no urethrocutaneous fistulation was reported in their case. It has been suggested that clitoral piercing induces changes in the periurethral microflora.…”
Section: Case Reportsupporting
confidence: 90%
See 1 more Smart Citation
“…12 Differences in urinary microbiota composition between MGLSc patients and healthy controls have also in a separate study. 13 While our case demonstrates similarities with that reported by De Giorgi et al, no urethrocutaneous fistulation was reported in their case. It has been suggested that clitoral piercing induces changes in the periurethral microflora.…”
Section: Case Reportsupporting
confidence: 90%
“…12 Differences in urinary microbiota composition between MGLSc patients and healthy controls have also in a separate study. 13…”
Section: Case Reportmentioning
confidence: 99%
“…While this study represents the only study to date of both the balanopreputial microbiota and urinary microbiota, Cohen et al . investigated the urinary microbiota of men with urethral MGLSc and demonstrated a unique microbiota profile in MGLSc compared with controls, with enrichment of the orders Bacillales , Bacteroidales , and Pasteurellales 51 . They did not report any differences in the relative abundance of the order Fusobacteriales .…”
Section: Discussionmentioning
confidence: 95%
“…In penile cancer, Onywera et al have described a higher a greater relative abundance of Prevotella, Peptinophilus and Dialister and lower relative abundance of Corynebacterium in hrHPV-infected men [67]. Cohen et al found that the urine bacteriome of male LS patients with showed enrichment of Bacillales, Bacteriodales and Pasteurellales [68]. Increased incidence of Epstein-Barr virus (EBV) in LS biopsy tissue has been described in both female (26.5%) and male (37-38.3%) LS patients [69][70][71].…”
Section: Discussionmentioning
confidence: 99%